Philippine Economic Interest in China Through Belt and Road Initiative Framework in 2018 - Sumadi, Kadek Ari; Sushanti, Sukma; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study tries to discuss the economic interests of the Philippines towards China through the framework of the Belt and Road Initiative. In reviewing this research, the researcher uses two concepts, namely: first, Donald E. Nuechterlein's concept of national interest, which explains that interests are a complex need of a country in relation to other countries that are outside its external environment. Second, the concept of Foreign Direct Investment, which explains that foreign direct investment can be a bridge to advance the economic growth of a country from foreign investors in the long term. The results of this study indicate that economic interests are prioritized by the Philippines against China, especially through the Belt and Road Initiative framework. This is indicated by encouraging an increase in the value of export-import trade and direct investment, so that it can encourage the realization of infrastructure which is the Philippines' main goal. Not only that, by implementing the grand strategy pivot to China, BRI's cooperation also brings various beneficial benefits to the Philippine economy, both from tourism, human diversity, as well as improving the existence and status of the country.